Twelve irrigated lowland rice breeding lines possessing resistance genes for RYMV, bacterial blight and blast identified - CGIAR Research Program on Rice (2021)
12 elite irrigated lowland breeding lines were identified through QTL profiling to have favorable alleles of genes conferring resistance to RYMV 1-2, blast (pi33) and bacterial blight (Xa4). The lines can be used as parents in new crosses.